2021
DOI: 10.3389/fpsyt.2021.747031
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Non-suicidal Self-Injury in Chinese Adolescents: A Meta-Analysis

Abstract: Non-suicidal self-injury (NSSI) in adolescents is an increasing public health problem in China. We conducted a meta-analysis of studies on NSSI in Chinese adolescents (between 10 and 19 years) to examine factors associated with NSSI. Twenty-five papers including 30 separate studies with 186,447 participants were included for analysis. The results from a random-effects model showed a weak, but significant overall prediction of NSSI (OR = 1.734). There were significant associations between the following seven fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In addition, studies have shown the mediating role of depression on other factors (i.e., peer acceptance and frequent nightmares) and NSSI behavior in adolescents ( 69 , 70 ). Furthermore, post-traumatic stress disorder, dissociative disorders, obsessive-compulsive disorders, eating disorders, sleep disorders, and substance use disorders were also common co-occurring disorders in adolescents with NSSI ( 1 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have shown the mediating role of depression on other factors (i.e., peer acceptance and frequent nightmares) and NSSI behavior in adolescents ( 69 , 70 ). Furthermore, post-traumatic stress disorder, dissociative disorders, obsessive-compulsive disorders, eating disorders, sleep disorders, and substance use disorders were also common co-occurring disorders in adolescents with NSSI ( 1 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-suicidal self-injury (NSSI) is a common psychiatric behavioral problem that threatens adolescents' health. NSSI refers to behaviors that do not aim at suicide, intentionally and directly harm their body tissues and are not recognized by society and culture ( 1 ). Common types of NSSI include cutting, scratching, hitting, knocking, and burning themselves ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this theory, the occurrence of NSSI is not intended for suicide purposes; however, NSSI is closely related to SI, AS, and SB ( Hawton et al, 2003 ; Nock et al, 2008 ; Martin et al, 2010 ), where NSSI frequency, number of self-injury methods, and hopelessness are the strongest predictors of AS ( Victor and Klonsky, 2014 ; Coppersmith et al, 2017 ). Notably, NSSI is a risk factor for committing suicide among adolescents with depression ( Hawton et al, 2003 ; Zubrick et al, 2017 ; Fan et al, 2021 ; Masi et al, 2021 ). In particular, female adolescents have a higher risk of committing suicide if they exhibit frequent NSSI behaviors ( You and Lin, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same conclusion was drawn regarding depressive disorders that were vulnerable to NSSI ( Fox et al, 2015 ). Therefore, it is important to investigate predictors of NSSI in adolescents with depressive disorders for clinical risk assessment and therapeutic interventions ( Fan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%